I Am You the Hermeneutics of Empathy in Western Literature, Theology and Art. - Morrison, Karl F. (Princeton : Princeton University Press, 2014)
Important trends in contemporary intellectual life celebrate difference, divisiveness, and distinction. Speculative writing increasingly highlights ""hermeneutic gaps"" between human beings, their histories, and their hopes. In this book Karl Morrison identifies an alternative to this disruption. He explores for the first time the entire legacy of thought revolving around the challenging claim ""I am you""--Perhaps the most concise possible statement of bonding through empathy. Professor Morrison shows that the hope for thoroughgoing understanding and inclusion in another's world view is ce.
Cover; Contents; Introduction; Part I The Content of the Saying; 1. The Positive Content; Part II Patterns of Understanding; Part III Understanding Understanding: The Silence of Words; Part IV Understanding Understanding: The Invisibility of Art; Conclusion.
Print version record.
Keywords: Empathy in literature; Empathy in art; Empathy -- Religious aspects -- Christianity -- History of doctrines; HISTORY / World; LITERARY CRITICISM / Semiotics & Theory; Electronic books